Pengaruh Slow Deep Breathing terhadap Kecemasan Ibu saat Pemasangan KB Implan - HELEN MARSHANDA; RETNO DEWI PRISUSANTI; RIFZUL MAULINA (Hang Tuah Medical Journal, 2026)
The Family Planning (FP) program is a government initiative to control population growth through the use of long-term contraceptive methods, including implant contraception. However, fear and anxiety regarding pain during implant insertion often become barriers for acceptors. This study aimed to determine the effect of slow deep breathing relaxation techniques on anxiety levels of women during implant insertion at TPMB Afita Delianah, Turen, Malang Regency. A quantitative quasi-experimental study with a Nonequivalent Control Group design was conducted with 32 respondents divided equally into an intervention group and a control group. The intervention group received slow deep breathing exercises for 15 minutes before implant insertion, while the control group did not receive any intervention. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS) before and after the intervention. Data analysis included Shapiro-Wilk normality test, paired t-test, Levene’s homogeneity test, and Independent Sample T-Test. Results showed that before the intervention, the mean anxiety score of the intervention group was 28.75 and the control group was 27.88. After the intervention, the intervention group’s anxiety score significantly decreased to 20.00, while the control group only decreased to 27.13. Independent Sample T-Test results indicated that the reduction in anxiety was significantly greater in the intervention group compared to the control group (p < 0.05). These findings indicate that slow deep breathing relaxation is effective in reducing anxiety during implant insertion. This technique can serve as a practical, safe, and applicable non-pharmacological strategy in midwifery practice to enhance women’s psychological comfort during reproductive health procedures.